(untitled) (Altre Modernità, 2016)
Between 1961 and 1974 Portugal sustained a long-term colonial war, that was not public acknowledge, with Angola, Mozambique and Guinea-Bissau. After this conflict, a sudden process of decolonization occurred, following the revolution of 25th of April 1974, which ended the long-term dictatorship of the fascist regime and also the colonial war. This essay focuses on the reasons of this process of decolonization, its frames and reconfigurations and its impact in the Portuguese identity. The second part of this essay focuses on Portugal as a postcolonial European nation in direct confrontation and dialogue with other countries in the European Community that share a similar past, which affect Europe as a continent haunted by its colonial issues.